Microstructural features influencing failure in Macadamia nuts. Issue 2 (April 2012) - Fleck, C.; Schüler, P.; Meinel, D.; Zaslansky, P.; Currey, J. D.
Abstract : Macadamia nutshells exhibit surprisingly high strength making them interesting model materials for impact-resistant engineering structures. The properties of the nutshell are assumed to arise from the hierarchically organized microstructure. However, the relationship between microstructure and mechanical properties is not completely clear. We investigated the failure behavior of whole Macadamia integrifolia nutshells and specimens cut from the shell, under tension and compression loading. Deformation and fracture were observed by means of light and scanning electron microscopy and microtomography. The outer and inner sutures, the vascular bundles, and the interfaces between cells or cell bundles were shown to affect formation and growth of cracks and thereby they strongly modulate the strength. While the sutures act as weak links and notches increasing the local stresses, the vascular bundles both increase local stresses due to their notch effect, and also divert and even stop cracks. Cracks are further diverted by bundles of aligned fiber cells.